Ionospheric horizontal gradients effect and estimation from observations - Nagarajoo, Karthigesu (Penerbit UTHM, 2020)
Global Navigation Satellite System (GNSS) is the standard generic term for satellite navigation systems that provides autonomous geospatial positioning with global coverage. GNSS allows the earth-based receivers to determine their location using time signals transmitted along a line of sight by radio signals form satellites..